Launch of IFPRI’s Global Food Policy Report 2019: Overview - Fan, Shenggen (2019)
In partnership with the Faculty of Agriculture, Ain Shams University - The Launch of IFPRI’s Global Food Policy Report "Revitalizing Rural Areas in Egypt" - the seminar focused on the role of agricultural investments and policies for revitalizing Egypt’s rural areas.